The Scholarly Journal in the GDR : Politicizing the Zeitschrift für Anglistik und Amerikanistik (1953-1990) - Lörch, Michael (Literature and Cultural Studies E-Books Online, Collection 2026., 2025)
This volume goes beyond treating periodicals as mere sources of information and explores the forces shaping scholarly journals that typically remain hidden to their readers. It examines the four-decade run of the Zeitschrift für Anglistik und Amerikanistik ( ZAA ) in the German Democratic Republic using numerous, previously unpublished archival sources. It reveals how, beyond economics and academia, politics and ideology can play a decisive role in how a humanities journal is produced and read across borders. The volume thus provides an eye-opening look at the ways journals are shaped by much more than academic trends, not only in the context of the Cold War, but also today, in our increasingly politicized world.